Double fault - Jenkins, Jerry B.; Fabry, Chris, 1961- (Wheaton, Ill. : Tyndale House, 2005)
After joining a tennis camp at a local country club, twins Ashley and Bryce Timberline are blamed for outbreaks of vandalism there, and must work not only to clear their names, but also to find the real culprit.
4.5
3-6
Keywords: Christian life -- Fiction; Family life -- Colorado -- Fiction; Mystery and detective stories; Tennis -- Fiction; Twins -- Fiction; Vandalism -- Fiction; Christian fiction; Christian life -- Fiction; Family life -- Colorado -- Fiction; Mystery fiction; Tennis -- Fiction; Twins -- Fiction; Vandalism -- Fiction; Colorado -- Fiction; Colorado -- Fiction; Christian fiction; Mystery fiction